2019
DOI: 10.1108/ijhma-10-2018-0082
|View full text |Cite
|
Sign up to set email alerts
|

Modelling housing prices and market fundamentals: evidence from the Sydney housing market

Abstract: Purpose Housing prices in Sydney have increased rapidly in the past three decades. This leads to a debate of whether Sydney housing prices have departed from macroeconomic fundamentals. However, little research has been devoted to this area. Therefore, this study aims to fill this gap by examining the long-run association between housing prices and market fundamentals. Further, it also examines the long-run determinants of housing prices in Greater Sydney. Design/methodology/approach The analysis of this stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
34
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(39 citation statements)
references
References 60 publications
5
34
0
Order By: Relevance
“…When comparing the adjusted values, there are also no significant dissimilarities for particular estimation methods. In general, they range from 0.20 to 0.55, indicating good matching of the models to the data compared to other studies (see, e.g., Hwang & Quigley, 2006 ; Al-Masum & Lee, 2019 ). Furthermore, as Stevenson ( 2008 ) notes, not obtaining very high R 2 values in studies regarding the occurrence of house price bubbles is not worrisome because the purpose of this type of analysis is not to explain actually existing market movements but to model fundamental house prices.…”
Section: Resultssupporting
confidence: 69%
“…When comparing the adjusted values, there are also no significant dissimilarities for particular estimation methods. In general, they range from 0.20 to 0.55, indicating good matching of the models to the data compared to other studies (see, e.g., Hwang & Quigley, 2006 ; Al-Masum & Lee, 2019 ). Furthermore, as Stevenson ( 2008 ) notes, not obtaining very high R 2 values in studies regarding the occurrence of house price bubbles is not worrisome because the purpose of this type of analysis is not to explain actually existing market movements but to model fundamental house prices.…”
Section: Resultssupporting
confidence: 69%
“…Rahman (2008) classified housing factors into three broad categories, namely the short/cyclical, institutional and long-term variables, and concluded that interest rates, investment demand, existing economic climate are the short-term determinants, whereas economic growth and wealth effect are the long-term factors. In the most recent scholarly literature, Al-Masum and Lee (2019) revealed that population growth and lending are insignificant in explaining Sydney house prices in the long run, whereas Nguyen and Wang (2019) suggested that strong projected population growth will help sustain the Australian economy in the short run.…”
Section: Key Determinants Of Downturn 2018mentioning
confidence: 99%
“…According to Arestis et al (2017), the house price overvaluation might take place because of imbalance between demand and supply of housing. Although the housing sector is a crucial part of the economy, an accelerated growth of property values may be an indication of a housing bubble, which would have a detrimental effect on the economy (Al-Masum and Lee, 2019; Chen et al , 1986; Liu et al , 2017; Stevenson, 2008). This issue has created a hot debate among scholars and experts of housing economics.…”
Section: Literature Reviewmentioning
confidence: 99%